2017
DOI: 10.1038/s41598-017-01950-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenation of aldehydes to 3-propanal, propanol and propanoic acid derivatives

Abstract: Methodology has been developed for the synthesis of 3-propanaldehydes through a five-step process in 11–67% yield from aldehydes. Aldehydes were reacted with Meldrum’s acid through a Knoevenagel condensation to give materials that upon reduction with sodium borohydride and subsequent hydrolysis decarboxylation generated the corresponding 3-propanoic acid derivatives. The -propanoic acid derivatives were reduced to give 3-propanol derivatives, which were readily oxidised to target 3-propanal derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The final step produced high yields (96–98%) of alkyl derivatives of Meldrum’s acid ( 5a,b ) from compound 3 when it was treated with alkyl bromide ( 4a,b ) in a DMF solvent with potassium carbonate as a base for 18 h at room temperature (Table ). ,, …”
Section: Resultsmentioning
confidence: 99%
“…The final step produced high yields (96–98%) of alkyl derivatives of Meldrum’s acid ( 5a,b ) from compound 3 when it was treated with alkyl bromide ( 4a,b ) in a DMF solvent with potassium carbonate as a base for 18 h at room temperature (Table ). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Two carbon elongation of aldehyde to carboxylic acid by Knoevenagel condensation with 14 , reduction of olefin, and decarboxylation has already been reported in the literature, but analogous reactions starting from ketone have not been reported yet . The key synthetic challenge in the above route was the diastereoselective reduction of 12 .…”
Section: Introductionmentioning
confidence: 93%
“…[26] Another method for the synthesis of HCAL and its derivatives (11-67% yield) is through a five-step process from the Knoevenagel condensation of aldehydes with Meldrum's acid. [30] Moreover, Frost et al reported the hydrosilylation of Meldrum's acid by a multi-step process, using palladium or molybdenum catalysts. [31,32] Instead of these complex multi-step processes, selective hydrogenation of CAL to a HCAL reaction does not produce any corrosive byproduct or toxic waste.…”
Section: Introductionmentioning
confidence: 99%